Legal Review of the Obligation to Install Boundary Signs For Land Rights Owners - M. Husin; Amin Purnawan (Jurnal Hukum Khaira Ummah, 2025)
The background of this thesis is that land is a very basic human need. Humans live and carry out activities on land so that at all times humans are always in contact with land. It can be said that almost all human life activities, both directly and indirectly, always require land. Land is so important for human life, that everyone will always try to own and control it. With this, it can give rise to land disputes in society. Land registration is carried out according to the provisions stipulated in Government Regulation Number 24 of 1997 concerning Land Registration. In this thesis the author raises the following problems: how is the obligation to install boundary markers for land owners based on Government Regulation Number 24 of 1997 concerning Land Registration, the factors causing land owners to not install boundary markers and the legal consequences that arise if the installation of boundary markers for land owners is not carried out. The method used in this research is the sociological juridical method, namely legal research conducted by only examining library materials or secondary data. Sources of legal materials, namely data obtained from library materials by reading and reviewing library materials. The installation of boundary markers is carried out by the applicant after obtaining the consent of the adjacent owner. The installation of boundary markers and their maintenance are the responsibility of the applicant. The legal theories used in this study are the theory of legal responsibility and the theory of legal certainty. Factors causing landowners not to install land boundary markers: lack of understanding, costs, difficulty in access, legal uncertainty, cultural and traditional factors, disagreements with other landowners, lack of socialization, technical difficulties, no proof of legal ownership, negligence or irresponsibility. The legal consequences that arise if the installation of boundary markers is not carried out for landowners are: the emergence of land boundary disputes, legal uncertainty, weakening of evidence, difficulty in re-measurement, the risk of land grabbing and administrative obstacles. In Islam, grabbing land belonging to another person or group of people, or taking it in ways that are not justified by religion, law and community norms, including injustice, which needs to be resolved fairly and in relation to the rights of fellow human beings.